German technology policy, innovation, and national institutional frameworks - David Soskice (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1996)
The pattern of innovation in Germany is substantially different from that in the US and the UK. It is argued that German patterns of innovation - incremental innovation in high quality products especially in engineering and chemicals - require long-term capital, highly cooperative unions and powerful employer associations, effective vocational training systems and close long-term cooperation between companies and with research institutes and university departments. (The more radical high-technology innovation typical of the US and the UK benefits by contrast from less regulated market conditions.) These conditions are met by the incentives and constraints of the institutional framework in which companies located in Germany are embedded. It is suggested that German technology policy is appropriate to and important for this pattern of high-quality incremental innovation. Moreover, the institutional framework - especially the role of powerful business associations - can solve the collective action problems to which German-type technology policy would normally be exposed. – – Die Entwicklungsvoraussetzungen für Innovationen in Deutschland unterscheiden sich substantiell von dem entsprechenden Muster in den USA oder in Großbritannien. In dem Papier wird die Meinung vertreten, daß die in Deutschland vorherrschenden Formen von Innovationen - Entwicklungen in kleinen Schritten bei technischen und chemischen Spitzenprodukten - langfristiges Kapital, sehr kooperative Gewerkschaften und mächtige Arbeitgeberverbände, ein effizientes Berufsausbildungssystem und eine enge langfristige Zusammenarbeit zwischen Unternehmen einerseits und Forschungsinstituten bzw. Universitätseinrichtungen andererseits voraussetzt. (Den für die USA und Großbritannien typischen hochtechnologischen Basisinnovationen sind im Gegensatz dazu geringer regulierte Marktbedingungen förderlich.) Diese Bedingungen werden durch die Anreize und Beschränkungen des Institutionengefüges, in dessen Rahmen die Unternehmen in Deutschland arbeiten, erfüllt. Es wird in dem Papier die These vertreten, daß die Technologiepolitik in Deutschland angemessen und wichtig für den beschriebenen Innovationstyp ist. Darüber hinaus kann das Institutionengefüge - vor allem die mächtigen Unternehmensverbände - die "collective-action- Probleme lösen, denen die in Deutschland vorherrschende Technologiepolitik normalerweise ausgesetzt wäre.
Keywords: 330